Pemberdayaan Kelompok Usaha Keripik Desa Kendalpayak Kecamatan Pakisaji Kabupaten Malang - Rusno Rusno; Yoyok Seby Dwanoko; Roni Alim. B. A (Jurnal ABM Mengabdi, 2018)
Kendalpayak Village, Pakisaji Subdistrict, Malang Regency is a strategic and potential village to be made into the Central Village of Chips. There are two PKM partners in this village, namely: (1) a partner of the cassava chips group "Cap Kunci", managed by Mr. Misbachul Munir 37 years and (2) business group partners "Kripset Si Iteng", managed by Mr. Opid 45 year. In line with the increasingly tight competition of UKM, there are obstacles faced by these business groups, such as: production, marketing and financial management. The solution given to partners for aspects of production is increasing the quantity and quality of products by making tastes better and more variants. Marketing is done with online media / market expansion and packaging that follows market trends. As for financial management problems, managerial and bookkeeping are well planned. It is expected that with this PKM program, both partners can increase production, innovate chips packaging design, expand marketing networks, manage finances independently and evaluate.